Upolitycznienie wyższych uczelni - Drozdowicz, Zbigniew (My University, 2017)
In the first part of these remarks I recall such examples from the past of the mentioned political agenda that might be a sort of warning for a too far reaching overtaking of higher education institutions by political powers. In the second part however I recall contemporary ways and forms of political agenda which I call “velvet” revolutions and I also see them as threat to fulfill by universities their social missions. The remarks and evaluations formulated by me at the end are certainly not to be considered as undiscussable. These remarks are being treated by me as a voice in the discussion on the issue how much politics might be or has to be in the life of universities and what kind of politics do any good to them and what kind brings more damage.
Keywords: politicizing the universities; historical casuses; „velvet” revolutions